A wash-free SNAP-tag fluorogenic probe based on the additive effects of quencher release and environmental sensitivity. Issue 48 (31st May 2017) - Leng, Shuang; Qiao, Qinglong; Miao, Lu; Deng, Wuguo; Cui, Jingnan; Xu, Zhaochao
Abstract : A 1, 8-naphthalimide-derived SNAP-tag fluorogenic probe can specifically and rapidly label proteins in live cells without requiring a wash procedure. Abstract : A 1, 8-naphthalimide-derived fluorogenic probe was reported to label SNAP-tag fusion proteins in living cells. The probe can rapidly label a SNAP-tag and exhibit a fluorescence increase of 36-fold due to the additive effects of environment sensitivity of fluorophores and inhibition of photo-induced electron transfer from O 6 -benzylguanine to the fluorophore. The labeling of intracellular proteins has been successfully achieved without a wash-out procedure.